FY 2020 Turkey Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2022)
The Country Opinion Survey in Turkey assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Turkey perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Turkey on 1) their views regarding the general environment in Turkey; 2) their overall attitudes toward the WBG in Turkey; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Turkey; and 4) their perceptions of the WBG’s future role in Turkey.